2022
DOI: 10.3389/fonc.2022.889159
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Protein 1 Regulates Colorectal Cancer Cell Proliferative, Migratory, Invasive and Epithelial-Mesenchymal Transition Activities Through the PI3K/AKT/GSK3β/Snail Signaling Axis

Abstract: In prior reports, extracellular matrix protein 1 (ECM1) upregulation has been reported in colorectal cancer (CRC) patient tumor tissues, and has been suggested to be related to the metastatic progression of CRC, although the underlying mechanisms have yet to be clarified. In this study, we found that ECM1 was overexpressed in both CRC tissues and cell lines. Upregulation of ECM1 was correlated with tumor size, lymph node status and TNM stage in CRC patients. Knocking down ECM1 suppressed CRC cell growth, migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(27 reference statements)
0
6
1
Order By: Relevance
“…In our previous study, we found that ECM1 could promote CRC progression by influencing cell growth, metastasis and the process of EMT ( Long et al, 2022 ). As a result, we postulated that cell apoptotic evasion and EMT might be regulated by ECM1 in the HCT15/FU cells with mesenchymal-like phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we found that ECM1 could promote CRC progression by influencing cell growth, metastasis and the process of EMT ( Long et al, 2022 ). As a result, we postulated that cell apoptotic evasion and EMT might be regulated by ECM1 in the HCT15/FU cells with mesenchymal-like phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AKT/GSK3β signaling was found to be activated in CRC-resistant cells and controlled HIF1α expression ( Shi et al, 2022 ). Moreover, ECM1 has been shown to regulate PI3K/AKT/GSK3β/Snail signaling in CRC ( Long et al, 2022 ). In line with these investigations, we found that ECM1-regulated 5-FU resistance in CRC was mediated through PI3K/AKT/GSK3β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, more and more studies have shown that EMT is involved in the proliferation of CSCs, which further promotes cancer progression [ 14 ]. In previous studies, the PI3K/AKT signaling axis was found to be indispensable for EMT induction and subsequent tumor progression [ 15 ]. The PI3K/Akt pathway is related with CRC progression, but the specific molecular mechanism is unclear [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…ECM1 inhibition down regulated Snail, pGSK3β, and p-AKT in CRC cells. Additionally, ECM1 induced CRC metastasis by promoting EMT via modulating the PI3K/AKT/GSK3β/Snail pathway [ 42 ]. P2X purine receptors are ATP-dependent cation channel receptors that regulate potassium ions outflow and sodium and calcium ions influx [ 114 116 ].…”
Section: Pi3k/akt/gsk-3β Axismentioning
confidence: 99%